Generative AI in Higher Education: Challenges and Opportunities for Course Learning - Zhang, Jinbao (Advances in Social Sciences Research Journal, 2025)
Generative Artificial Intelligence (GenAI) is transforming course learning in higher education. This study, based on two rounds of action research in two college courses, reveals critical challenges in this transformation. Findings indicate that students' reliance on GenAI can hinder their autonomy, critical thinking, and affective-social learning, while also raising concerns about content accuracy, intellectual property rights, and privacy. Although teacher guidance partially mitigates these issues, enhanced strategies are crucial. This study provides practical implications for optimizing curriculum design, teaching methods, and evaluation criteria, emphasizing the need to incorporate ethics education and strengthen emotional-social guidance. Future research directions are suggested to address the challenges of GenAI and ensure educational quality and student development.